Aktivitas Mikroba Tanah, Pertumbuhan dan Rendemen Nilam (Pogostemon Cablin Benth.) pada Berbagai Aras Bahan Organik Serta Lengas Tanah di Ultisols - Any Kusumastuti (Jurnal Penelitian Pertanian Terapan, 2013)
This experiment has been conducted to study the effect of organic matter levels and soil water content levels of Ultisols on soil microbe activity, growth and patchouli oil content of Pogostemon cablin. Experiment was carried out under green house condition and was arranged in completely randomized blocks with factorial design, consisted of two factors and tree replications. First factor was levels of organic matter (5, 7.5, and 15 ton hectare-1), and second factor were levels of soil water content (100 %, 80 %, 60 % and 40 % of field capacity). The yield of experiment showed that there were interaction between organic matter levels and soil water content levels on dry weight, wet weight of Pogostemon cablin and CO2 releasing but there were no interaction on dry weight and wet weight of root of Pogostemon cablin. The highest patchouli oil content (i.e. 1.35 %) are found on 100 % level of soil water content, but on lower levels of soil water content, patchouli oil content were decrease. Keywords: Soil microbe activity, patchouli oil, pogostemon cablin, organic matter